TINGKAT KETERAMPILAN BERMAIN FUTSAL PEMAIN EKSTRAKURIKULER SMP KARTIKA XX-2 MAKASSAR - Suhardianto, Suhardianto; Janwar, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The problem in this research was that there had never been a test on the futsal playing skills of Extracurricular Players at SMP Kartika XX-2 Makassar. This research aims to determine the level of futsal playing skills of participants who take part in extracurricular activities at SMP Kartika XX-2 Makassar. This research is a descriptive study activity (survey) which was carried out in one meeting and contained several tests, namely: passing, dribbling, control and shooting. This research data is the result of passing, dribbling, control and shooting tests which were carried out twice using seconds. The data source for this research is the Kartika XX-2 Makassar Middle School players who take part in futsal extracurricular activities, totaling 30 players. Data collection for this research used instruments from Agus Susworo's source which included: Dribbling from post 1 to post 4 or the ball stopped, passing test without stopping 10 times, one cone turning left and one cone turning right to form the number 8, passing stopping test 10 times. using the right foot and left foot, shooting the goal once using the right foot and once the left foot. These results show that in the very good category there is 1 player or 3.3%, in the good category there are 6 players or 20%, in the fair category there are 17 players or 56.7%. Meanwhile, the less and less categories each have 3 players or 10%.